Insecticide susceptibility of the dengue vector Aedes aegypti (Diptera: culicidae) in Makkah City, Saudi Arabia - Al Thbiani, Aziz; Dieng, Hamady; Ahmad, Abu Hassan; Satho, Tomomitsu; Miake, Fumio; Md Rawi, Che Salmah; Sazaly, AbuBakar (Elsevier (Singapore) Pte Ltd, 2011)
Objective To examine the insecticide susceptibility of Aedes aegypti (Ae. aegypti) from various sites in Makkah City, Saudi Arabia. Methods This was examined based on WHO standard procedures. Results The larvae of Ae. aegypti were susceptible to all larvicides examined, but this susceptibility was more pronounced in wild populations, which tended to show tolerance to icon. Icon was the most effective larvicide with LC50 values of 0.007 ppm and 0.012 ppm for the laboratory and field strains, respectively. Ae. aegypti adults exposed to lambda-cyhalothrin showed a low mortality rate in comparison with those exposed to deltamethrin and cyfluthrin. Conclusions The results of the present study indicate differential susceptibility between field and laboratory larval populations. Wild larvae are less susceptible to insecticide treatments than their laboratory-bred counterparts. Taken together, these results suggest that tolerance and the tendency toward resistance to commonly used insecticides are present in Ae. aegypti populations throughout Makkah City, Saudi Arabia.